Bioactivities, Mechanisms, Production, and Potential Application of Bile Acids in Preventing and Treating Infectious Diseases - Shuang Liu; Shuo Yang; Biljana Blazekovic; Lu Li; Jidan Zhang; Yi Wang (Engineering, 2024)
Infectious diseases are a global public health problem, with emerging and re-emerging infectious diseases on the rise worldwide. Therefore, their prevention and treatment are still major challenges. Bile acids are common metabolites in both hosts and microorganisms that play a significant role in controlling the metabolism of lipids, glucose, and energy. Bile acids have historically been utilized as first-line, valuable therapeutic agents for related metabolic and hepatobiliary diseases. Notably, bile acids are the major active ingredients of cow bezoar and bear bile, which are commonly used traditional Chinese medicines (TCMs) with the therapeutic effects of clearing heat, detoxification, and relieving wind and spasm. In recent years, the promising performance of bile acids against infectious diseases has attracted attention from the scientific community. This paper reviews for the first time the biological activities, possible mechanisms, production routes, and potential applications of bile acids in the treatment and prevention of infectious diseases. Compared with previous reviews, we comprehensively summarize existing studies on the use of bile acids against infectious diseases caused by pathogenic microorganisms that are leading causes of global morbidity and mortality. In addition, to ensure a stable supply of bile acids at affordable prices, it is necessary to clarify the biosynthesis of bile acids in vivo, which will assist scientists in elucidating the accumulation of bile acids and discovering how to engineer various bile acids by means of chemosynthesis, biosynthesis, and chemoenzymatic synthesis. Finally, we explore the current challenges in the field and recommend a development strategy for bile-acid-based drugs and the sustainable production of bile acids. The presented studies suggest that bile acids are potential novel therapeutic agents for managing infectious diseases and can be artificially synthesized in a sustainable way.